Prevalence and Incidence of Heart Failure Among Urban Patients in China: A National Population-Based Analysis - Wang, Hua; Chai, Ke; Du, Minghui; Wang, Shengfeng; Cai, Jian-Ping; Li, Yingying; Zeng, Ping; Zhu, Wanrong; Zhan, Siyan; Yang, Jiefu (Circulation. Heart failure, 2021)
Large-scale and population-based studies of heart failure (HF) incidence and prevalence are scarce in China. The study sought to estimate the prevalence, incidence, and cost of HF in China. We conducted a population-based study using records of 50.0 million individuals ≥25 years old from the national urban employee basic medical insurance from 6 provinces in China in 2017. Incident cases were individuals with a diagnosis of HF (International Classification of Diseases code, and text of diagnosis) in 2017 with a 4-year disease-free period (2013-2016). We calculated standardized rates by applying age standardization to the 2010 Chinese census population. The age-standardized prevalence and incidence were 1.10% (1.10% among men and women) and 275 per 100 000 person-years (287 among men and 261 among women), respectively, accounting for 12.1 million patients with HF and 3.0 million patients with incident HF ≥25 years old. Both prevalence and incidence increased with increasing age (0.57%, 3.86%, and 7.55% for prevalence and 158, 892, and 1655 per 100 000 person-years for incidence among persons who were 25-64, 65-79, and ≥80 years of age, respectively). The inpatient mean cost per-capita was $4406.8 and the proportion with ≥3 hospitalizations among those hospitalized was 40.5%. The outpatient mean cost per-capita was $892.3. HF has placed a considerable burden on health systems in China, and strategies aimed at the prevention and treatment of HF are needed. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: ChiCTR2000029094.